WATERWORKS OF PREHISPANIC PERIOD IN HUACCANA, CHINCHEROS - APURIMAC - Vivanco Pomacanchari, Cirilo (2015)
In quchakuna waterworks gaps in pre-Hispanic Peru they are admirable, in the long process of Andean cultures until the time the tawantinsuyu Inka. Before the Spaniards arrive to the Andes, any contentions infrastructure was implemented in South America than in Peru, the quality artificial lakes dammed for irrigation and human consumption. The aim is to detail the construction techniques, function and components of the levees in the lagoons, which are the archaeological indicators and expectations, organized in contexts installation and association, architectural features and sedimentology. The result of the study of dams in the gaps on the supply of water, related to farming activities and domestic use are engineering works, arranged and constructed with proprietary technology of ancient Andean world and the raw material of the place. In conclusion, they are water works to expand, fix the mirror of water and defy natural anomalies in the daily work of man in ancient Peru.